Development of Phylodynamic Methods for Bacterial Pathogens. Issue 9 (September 2021) - Ingle, Danielle J.; Howden, Benjamin P.; Duchene, Sebastian
Abstract : Phylodynamic methods have been essential to understand the interplay between the evolution and epidemiology of infectious diseases. To date, the field has centered on viruses. Bacterial pathogens are seldom analyzed under such phylodynamic frameworks, due to their complex genome evolution and, until recently, a paucity of whole-genome sequence data sets with rich associated metadata. We posit that the increasing availability of bacterial genomes and epidemiological data means that the field is now ripe to lay the foundations for applying phylodynamics to bacterial pathogens. The development of new methods that integrate more complex genomic and ecological data will help to inform public heath surveillance and control strategies for bacterial pathogens that represent serious threats to human health. Highlights: Bacterial pathogens are responsible for a significant proportion of the global disease burden, with genomic surveillance increasingly used. Increased antimicrobial resistance in bacterial pathogens represents an urgent public health threat. Current analyses of bacterial genomes consist of mapping metadata to phylogenetic trees, without explicit models for how such metadata evolved. Phylodynamic methods are underdeveloped in bacteria, despite a wealth of genome sequences and metadata now available, due to the relatively more complex evolutionary dynamics compared with viruses. Development of phylodynamic methods for bacteria and a better understanding of those available for viruses will be a fruitful area of research. The translation and application of developed methods will have potential to revolutionize how these data are used to address public health threats.